Analysis Of The Relationship Between CFT, SDT, and PRT Theories and Esg Factors and Their Impact On Sustainable Financial Performance In The Private - Ahmed Issa Dheyab AnsafSoft (Penerbit Jurnal Indonesia, 2026)
This study aims to demonstrate the relationship between Environmental, Social, and Governance (ESG) factors and the cash flow theory, justified progress theory, and resource theory, and their impact on sustainable financial performance. It also examines the relationship between these three theories and ESG factors, and how companies can leverage these relationships to achieve sustainable financial performance. The study shows that cash flow theory plays a crucial role in the efficiency and effectiveness of liquidity and operations for achieving sustainable financial performance. Resource theory offers an internal perspective that focuses on the use of business resources to enhance efficiency and financial sustainability. Sustainable development theory provides a comprehensive framework that integrates environmental, social, and economic dimensions into corporate policies and strategies. Furthermore, the results show that a positive interaction between key environmental, social, and economic elements and a company's operational activity contributes to improved cash flow, positively impacting long-term financial performance. The study also demonstrates that adopting ESG factors adds value and reduces investment risk. The study recommends integrating ESG factors into financial planning and developing non-financial performance measurement tools, given their direct impact on enhancing the financial and operational sustainability of companies in the industrial sector